Safety and feasibility of a 7F thin-walled sheath via distal transradial artery access for complex coronary intervention - Zong, Bin; Liu, Yi; Han, Bing; Feng, Chun-Guang (Frontiers in Cardiovascular Medicine, 2022)
Background: Compared with traditional transradial artery access (TRA), there are limited data that can confirm the efficacy and safety of a 7F thin-walled sheath placed via distal TRA (dTRA) for percutaneous coronary intervention (PCI). Objective: To analyze the safety and efficacy of the placement of a 7F thin-walled sheath via dTRA for PCI. Methods: This was a single-center retrospective observational study in which 102 patients who received complex PCIs with a 7F thin-walled sheath placed via dTRA in the catheter room of our hospital from May 2020 to October 2021 were included. The basic information, puncture success rate, radial artery occlusion (RAO) rate, radial artery lumen diameter and area, surgical data, pain score, and complication rate were observed and recorded. Results: The puncture success rate was 90.2% in the 102 patients, and the success rate of the operation was 97.8% among 92 patients with a successful puncture. The PCIs for patients included emergency PCI and all types of complex PCIs. Color Doppler ultrasound performed at 1 and 30 d after the procedure showed that the RAO rate was 2.2%, the distal RAO rate was 3.3%, the postoperative average pain score was 2.2 points, and there were five patients (5.4%) with local hematoma, all of which were grade 1–2. Radial artery spasm and nervous injury occurred in two patients (2.2%), and arteriovenous fistula occurred in one patient (1.1%). Radial artery perforation, radial artery dissection, pseudoaneurysm, and sheath kinking did not occur. Conclusion: The placement of a 7F thin-walled sheath via dTRA for PCI showed a high puncture and procedural success rate, low postoperative RAO rate, and low incidence of local hematoma and other complications. The placement of a 7F Glidesheath Slender® via dTRA for PCI is safe and feasible.